The Rise and Fall of Swiss Unemployment: Relative Demand Shocks, Wage Rigidities, and Temporary Immigrants - Patrick A. Puhani (Institute for the Study of Labor (IZA), 2003)
Switzerland, traditionally a ?zero unemployment? economy, has seen an unprecedented rise in joblessness in the 1990s although unemployment fell again to a rather low level after 1997. This paper tests whether Switzerland experienced a negative relative net demand shock against the low skilled (like the US) during this period. It turns out that only workers with an educational level below apprenticeship were affected by such a shock. Furthermore, I test whether wages reacted flexibly to this shock and find that they were rigid, which can explain the relative unemployment increase for this group. Finally, I test whether the skill mix of temporary immigrants was adjusted to the relative demand shock. The evidence suggests that it was changed during the period around 1997 when unemployment peaked. By 2001, however, the educational mix of temporary immigrants was not significantly different from its 1991 level any more, although relative unemployment for the least skilled was still relatively high in face of the relative wage rigidity affecting this group.
Keywords: E24; J21; J31; J64; 330; earnings; non-employment; rigidity; identification; foreigners; work permits; Arbeitslosigkeit; Ungelernte Arbeitskräfte; Gesamtwirtschaftliche Nachfrage; Schock; Lohnrigidität; Ausländische Arbeitskräfte; Internationale Arbeitsmobilität; Schätzung; Schweiz